Gender differences in scientific productivity of academic scientists in the Philippines.[article]. - Valencia, Marshall N.
Gender differences in scientific productivity were examined for a sample of 96 PhD science faculty members of the Philippines' largest research university. Productivity was measured using ISI abstracted journal publications for the period 1998-2002 and gender differences were determined for various personal, contextual, and social cognitive variables. Results indicated that males and females in the sample generally did not differ in scientific productivity levels as well as in most other variables considered. The findings were discussed int he context of its support to the deficit model of gender differences in scientific productivity. It was concluded that the sexes do not differ in the capacity and potential to be scientifically productive but they possibly differ in their pathways to publishing. -- (from the author)